2022
DOI: 10.1101/2022.09.02.22279479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related differences in cancer relative survival in the US: a SEER-18 analysis

Abstract: Importance: In the United States (US) in 2017, nearly half a million adults aged 75 and older were diagnosed with cancer. Cancer survival has improved since the 1990s, but to different extents across age groups, with a disadvantage for older adults. Documenting age-related differences in cancer survival in the US can help to inform prioritization efforts to narrow the age-related gap in cancer survival. Objective: To quantify age-related differences in relative survival by stage at diagnosis for 10 cancer type… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…3 Consistent with our findings, increasing age-related differences in colon and rectal cancer survival with worsening stage of diagnosis and large differences for unstaged diseases have been observed in ICBP and other countries, 5,3,13 which have also been shown for other cancer types in the US. 19 Regarding sex, the greater age-related differences in colon cancer survival in females with distant disease than males were also observed in New Zealand and Finland. 5,20 Some authors have suggested a possible involvement of sex hormones, but no causal mechanisms have been identified so far.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3 Consistent with our findings, increasing age-related differences in colon and rectal cancer survival with worsening stage of diagnosis and large differences for unstaged diseases have been observed in ICBP and other countries, 5,3,13 which have also been shown for other cancer types in the US. 19 Regarding sex, the greater age-related differences in colon cancer survival in females with distant disease than males were also observed in New Zealand and Finland. 5,20 Some authors have suggested a possible involvement of sex hormones, but no causal mechanisms have been identified so far.…”
Section: Discussionmentioning
confidence: 86%
“…Consistent with our findings, increasing age-related differences in colon and rectal cancer survival with worsening stage of diagnosis and large differences for unstaged diseases have been observed in ICBP and other countries, 5,3,13 which have also been shown for other cancer types in the US. 19…”
Section: Discussionmentioning
confidence: 99%